Transdermal Delivery of Fluconazole ß-cyclodextrin Complex Incorporated in Aloe vera Gel for Fungal Therapy: Development, Characterization and in vitro Evaluation - Aswal, Deepak; Bisht, Tanuja (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: The aim of the present investigation was to increase the dissolution rate of Fluconazole by solid dispersion technique and then it was incorporated into the gel for better diffusion profile. Fluconazole, an imidazole derivative, is used for the treatment of various local and systemic fungal infections. Materials and Methods: FTIR reports suggested the compatibility between the drug and the excipients. Among all the twelve solid dispersions formulations (F1-F12) prepared by two different methods, F-3 showed best results which were formulated by solvent evaporation method using β-cyclodextrin. This optimized formulation was then incorporated into Aloe vera gel and was evaluated for various parameters like drug content, pH, viscosity, spreadability, extrudability, in vitro diffusion study, in vitro release kinetics, antifungal and stability studies. Results: The gel formulation, GF1, exhibit high drug content (94%±1.30) and acceptable viscosity value of 9166.97±491cps. The pH of the gel formulation was 6.88±0.07 and exhibited better extrudability and spreadability. The diffusion rate and antifungal activity of GF1 were compared with the marketed formulation (FLUKIN). The GF1 formulation exhibited a faster diffusion rate i.e., 96.92% than the marketed formulation i.e. 89.24%. Also, the zone of inhibition by GF1 was of diameter 30mm which is again higher than the marketed formulation (24mm). Conclusion: Overall, it was observed that dissolution of Fluconazole was enhanced and the Aloe vera gel showed better diffusion profile and antifungal activity.
Keywords: Fluconazole; β-cyclodextrin solid dispersion; Solvent evaporation; Aloe vera; PVP; Solubility enhancement; Transdermal delivery